Analysis of Dangerous Mistakes in Discussion Activities - Refa Lina Tiawati; Suryanti Suryanti (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the analysis of language errors of Baubau 3 High School students in class discussion activities. The research design is descriptive qualitative. Research data analyzes language errors in class discussion activities in the form of use of intonation / tone, diction (choice of words), and sentence structure.The results showed that the form of language error analysis in class X of SMA Negeri 3 Baubau in class discussion activities was the use of intonation consisting of: high intonation, moderate intonation and low intonation. The use of diction (word choice) which consists of: the use of synonymous words, the use of denotation and connotation words, the use of foreign words or terms, the use of popular words and study words, and the use of words of conversation and slang. The use of  sentence structure consists of: the use of compulsory sentence structures and the use of sentence structures are not mandatory (where they like). Based on the data obtained regarding the analysis of language errors in class X students in class discussion activities, it can be said that in the use of intonation there are errors in the form of high intonation of 11, intonation is not there and intonation is low as many as 16 errors. In the use of diction there are errors in the use of 40 synonymous words, use of denotations and connotations of 41, use of foreign words or terms as many as 14, use of popular words and study words as many as 3, and the use of 120 words of conversation and slang. Furthermore, the use of sentence structures has errors in the form of mandatory sentence structures that do not exist, and in the sentence structure is not mandatory as many as 156 errors.